2007
DOI: 10.1136/bjo.2007.122416
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related quality of life in patients with diabetic macular oedema

Abstract: Type 2 diabetes patients with macular oedema experience a decreased VR-QOL compared with type 1 diabetic patients with diabetic retinopathy, glaucoma or cataracts. However, VR-QOL in type 2 diabetic patients with macular oedema was similar to those individuals with ARMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 21 publications
5
87
3
3
Order By: Relevance
“…However, it increased two months after the surgery and at follow-up. The studies by Hariprasad et al and Hirneiss et al in Germany revealed that visual acuity and vision-related quality of life before retinal surgery in various retinal disorders, such as macular degeneration and retinopathy, decreased (44,45). The results of this study are not consistent with the present research findings.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it increased two months after the surgery and at follow-up. The studies by Hariprasad et al and Hirneiss et al in Germany revealed that visual acuity and vision-related quality of life before retinal surgery in various retinal disorders, such as macular degeneration and retinopathy, decreased (44,45). The results of this study are not consistent with the present research findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Worth noting is the fact that NEI VFQ-25, although not the UAB-LLQ and WPAIQ, has been used previously to study the effects of diabetic retinopathy on vision-related quality of life. [15][16][17] However, as these data were generated from 55 community-and university-affiliated sites across the United States, we believe the patient-centered outcome responses are likely generalizable throughout the United States. Patients with the same clinical features from other countries may respond differently because of cultural influences on responses to these questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…4 It must be noted that of the visually disabling conditions in persons with diabetic eye disease, diabetic macular edema (DME), left untreated, is a common cause of vision loss.DME affects central vision and can lead to decline in vision ranging from slight visual blurring to blindness, substantially affecting independence and quality of life. 7,8 There are no comprehensive documentation, in available literature about prevalence, appearance, progression and associated visual loss in diabetic population with specific reference to macular edema.…”
Section: Introductionmentioning
confidence: 99%